Three computational approaches to weakly nonlocal Poisson brackets. Issue 4 (20th February 2020) - Casati, Matteo; Lorenzoni, Paolo; Vitolo, Raffaele
Abstract: We compare three different ways of checking the Jacobi identity for weakly nonlocal Poisson brackets using the theory of distributions, pseudo‐differential operators, and Poisson vertex algebras, respectively. We show that the three approaches lead to similar computations and same results.